The Effect of (Mental - Skillful) Exercises According to (Surface - Deep) Cognitive Representation in Attentional Control and Side Pass Skill of Handball for Junior - Ali Radhi Abdul Hussein; Mohammad Jasim Mohammad; Samer Youssef Mtaab (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in preparing (mental - skillful) exercises according to the cognitive representation (surface-deep), as the researchers believe that they affect the attentional control and side pass skill of handball for junior. Through the researchers’ interest in the handball game and its field followup to many training and educational units and matches, they noticed that a large number of young players face difficulty in focusing and diverting attention during matches, as well as in learning and mastering the side pass skill, which is difficult to perform and also to meet the needs and requirements of the game. As for research hypotheses: There is an effect of (mental - skillful) exercises according to the cognitive representation (surface - deep) in attention control and the skill of pushing to the side with hand reel for juniors. While the experimental method was used in solving the research problem, the research community was represented by the 16 players of the Kufa Junior Handball Club, and they were distributed into two groups equally by random method (lottery method), and then data processing using appropriate statistical means.